The Phenomenology of Assertive Behavior of Santri Dormitory Ainusyams Pondok Pesantren Darul Ulum Jombang in Facing Bullying - Zayn, Vilasufah; Yudianto, Andi; Mukarromah, Indah (PT Saintek Medika Nusantara, 2022)
UNESCO states that 1 in 3 children worldwide have experienced bullying. Bullying does not only occur in schools but also the pesantren environment. Students who experience bullying are students who are unable to behave assertively. This study aims to describe the assertive behavior of Ainusyams boarding students in dealing with bullying. The research design used is qualitative research with descriptive phenomenological methods. The social situation is the students of the Ainusyams boarding school, Darul Ulum Jombang, aged 13-17 years who have experienced bullying. Participants were seven female students who were victims of bullying using the Purposive Sampling technique. The research instrument uses the interview guidelines; data collection is done by observation, interview, and documentation. Data were analyzed using the Colaizzi method. This study resulted in 5 themes: telling the closest person, helplessness, expressing negative emotions, not wanting to find new problems, and distracting to positive things. It can be concluded that there are still incidents of bullying in pesantren, and the victims have not been able to behave assertively, as indicated by helplessness and inability to fight back.